In situ generating Cu2O/Cu heterointerfaces on the Cu2O cube surface to enhance interface charge transfer for the Rochow reaction. Issue 6 (22nd January 2021) - Tang, Fei; Li, Jing; Zhu, Yongxia; Ji, Yongjun; Li, Huifang; Liu, Hezhi; Wang, Xueguang; Zhong, Ziyi; Su, Fabing
Abstract : Cubic Cu/Cu2 O with heterointerfaces showed enhanced catalytic performance for the Rochow reaction. The resulting Schottky junction enhanced charge transfer efficiency and contributed to easier cleavage of Si–Si bond along {110} crystal plane. Abstract : In heterogeneous catalysis, successful design and construction of the desired oxide–metal interface are critical to catalytic function due to the significant interfacial effects. However, there are still challenges and obscurities in constructing and understanding the structure of various interfacial sites and their oxide–metal interactions. In the present work, a series of cubic Cu/Cu2 O hetero-nanoparticles were synthesized by in situ surface restructuring cubic Cu2 O nanoparticles via a simple reduction treatment. These nanoparticles were further used as the model catalyst for the Rochow reaction, an important industrial process for synthesizing organosilicon polymers. It is found that cubic Cu/Cu2 O with appropriate heterointerfaces exhibited improved dimethyldichlorosilane (M2) selectivity, Si conversion, and stability because of a strong interaction between the Cu/Cu2 O interface. The latter originates from the formation of Schottky junctions that enhance the charge transfer efficiency and the subsequent reduction of Cu + into Cu* (the active Cu atoms). Moreover, the easier cleavage of the Si–Si bond along the {110} crystal plane effectively generates Si* (the free Si atoms), which leads to inclined grooves on the surface of Si particles. The established transport and diffusion channels of Cu* and Si* greatly promoted the formation of the Cu3 Si active phase and the subsequent methyl chlorosilane. This work provides a new fundamental understanding of Cu-based catalysts for the Rochow reaction and reveals a clear relationship between the Cu2 O/metal heterointerface and the catalytic performance.